Grammatical Encoding in Bilingual Language Production: A Focus on Code-switching - Purmohammad, Mehdi (Frontiers in Psychology, 2015)
I report three experiments that examined whether words from one language of bilinguals can use the syntactic features form the other language and how such syntactic co-activation might influence syntactic processing. In other words, I examined whether there are any cases in which a lexical item inhibits its inherent syntactic feature and uses the syntactic feature(s) that belongs to the other language, instead. In the non-switch condition in experiment 1 and 2, Persian-English bilinguals described pictures using an adjective-noun string from the same language requested. In the switch condition, they used the nouns and adjectives from the other language. In Experiment 3, in the switch condition participants used only the adjectives of noun phrases from the other language. The results showed that bilinguals may inhibit the activation of a word’s syntactic feature and use the syntactic property from the other language instead (e.g., pirāhane (N) black). As the combinatorial node (the node that specify different kinds of syntactic structures in which a word can be used) of a used adjective retains activation at least temporarily, bilinguals are more likely to use the same combinatorial node even for an adjective from the other language. Using the syntactic features from the other language increased in the switch conditions. Moreover, more inappropriate responses observed when switching from bilinguals’ L2 to L1. The results also revealed that different experimental contexts may lead to different patterns of the control mechanism. The results will be interpreted in terms of Hartsuiker and Pickering’s (2008) model of syntactic representation